Photospheric plasma motions in the magnetic field of a single sunspot umbra - Gopasyuk, O.S.; Gopasyuk, S.I. (Кинематика и физика небесных тел, 2005)
The analysis of observed velocity fields in sunspots shows that the plasma motions above a sunspot umbra do not agree with the equation of continuity. We assumed that in the temperature minimum region above a sunspot umbra there is an effective diffusion of plasma across the lines of force in the region of the magnetic field. It leads to the formation of the steady flow of plasma in the temperature minimum, i.e., photosphere region. We determined the parameters in this steady flow. The calculated parameters do not contradict observational data on moving plasma in the magnetic field above a sunspot umbra.